2016
DOI: 10.1007/s00380-016-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized aortic conduits: could their cryopreservation affect post-implantation outcomes? A morpho-functional study on porcine homografts

Abstract: Explanted D grafts exhibited near-normal features, whereas the presence of calcification, inflammatory infiltrates, and disarray of elastic lamellae occurred in some DC grafts. In the unaltered regions of AVCs from both groups, almost complete re-endothelialization was observed for both valve cusps and aorta walls. In addition, side-by-side repopulation by recipient's fibroblasts, myofibroblasts, and smooth muscle cells was paralleled by ongoing tissue remodeling, as revealed by the ultrastructural identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…Having a cryopreserved organ increased the possibility of commercialization and benefit to a larger number of patients. Slow-cooling cryopreservation has already been used for successful preservation of decellularised scaffolds including the oesophagus 29 , 62 , 63 , but has never been applied to cell-seeded scaffolds. The same protocol was used here to cryopreserve constructs, after the first stage of the bio-engineering process, for 2 weeks in liquid nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Having a cryopreserved organ increased the possibility of commercialization and benefit to a larger number of patients. Slow-cooling cryopreservation has already been used for successful preservation of decellularised scaffolds including the oesophagus 29 , 62 , 63 , but has never been applied to cell-seeded scaffolds. The same protocol was used here to cryopreserve constructs, after the first stage of the bio-engineering process, for 2 weeks in liquid nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of cells in a cryopreserved ECM-derived scaffold could change the effect of the storage method on the structure, composition and biomechanical properties of the tissue of interest. Gallo et al decellularised porcine aortic valve conduits and randomised 12 Vietnamese Pigs to receive either decellularised or decellularised and cryopreserved conduits in a transplantation model [35]. No signs of dilatation, stenosis or regurgitation were seen in either group by echocardiography and cryopreserved conduits allowed cell repopulation and tissue renewal, although demonstrating signs of deterioration in some areas, suggesting a need to fine-tune the cryopreservation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Gallo et al reported finding spindle-shaped cells throughout the cusp interstitium when cellular AV allografts were im-planted in 12-month-old Vietnamese pigs for a period of 15 months. 24 In our study, we found that interstitial cells were repopulating the cusp, but that even after 12 months in vivo only the distal and middle sections of the cusps had been partially repopulated with host's cells. While cells infiltrating the wall were identified as mostly fibroblasts, the ratio of cells positive for SMA was higher in the cusps.…”
Section: Discussionmentioning
confidence: 40%